Living the Language: Self-Regulated Arabic Usage among Pesantren University Students in Indonesia - Segaf Baharun; Moh. Tohiri Habib (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2026)
Arabic language education in pesantren-based Islamic universities increasingly emphasizes self-regulated learning to encourage authentic language use beyond formal classrooms. However, empirical evidence on how learners independently sustain Arabic across social, academic, and digital domains remains limited, particularly in Islamic higher education contexts. This study examines the extent of self-regulated Arabic usage and identifies motivational, social, and digital factors supporting learner autonomy among university students in Indonesia. Using a convergent mixed-methods design, data were collected from 60 undergraduate students at Darullughah Wadda’wah International Islamic University, a pesantren-based institution in Pasuruan, East Java, Indonesia, through questionnaires, interviews, and observations. The findings reveal that 65% of students use Arabic daily in informal interaction, religious activities, and digital communication. Advanced learners show higher autonomous engagement (78.6%) compared to intermediate (64.0%) and beginner students (52.4%). Integrative motivation, peer support, and engagement with Arabic digital religious content significantly predict independent language use, while spontaneous oral production remains the main challenge. The study concludes that Arabic functions as a lived linguistic, academic, and spiritual identity practice in pesantren-based Islamic higher education. Practically, it recommends strengthening peer-supported language immersion and Arabic-based digital environments to sustain learner autonomy beyond classroom instruction.